Local Responses to Development Pressures: Conflictual Politics of Sprawl and Environmental Conservation - Gilbert, Liette; Wekerle, Gerda; Sandberg, L. (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 2005)
AbstractThere is an increasing opposition to the absorption of farmland and natural habitats by housing subdivisions and infrastructure, a symptom of urban sprawl. Through an analysis of these challenges at a regional scale, we address the contradictions and tensions in the politics of sprawl and environmental conservation. This article compares environmental conservation on the Oak Ridges Moraine in Richmond Hill and Caledon (two towns in the Greater Toronto Area) and argues that local political cultures, geography, and the density and political influence of citizens and social movements can have an impact on local responses to pressures of development. In the end, however, environmental activism in both towns is subjected to and shaped by an overall growth agenda.